Leasing of Agricultural Land Versus Agency Theory in the Light of Study Results - Renata Marks-Bielska; Agata Zielinska (Institute of Economic Research (IER), 2017)
Agency theory examines relations between entities as contract relations. The agency relation is always present when the situation of one person depends on the activities of another person. The individual who performs such activities is the agent, and the other party dependant on the activities of the agent is called the principal. The agency relation occurring between the above-listed parties is one of the oldest and most extensively codified modes of social interactions. Relationship studies: andlord - tenant, belong to the earliest and classic examples of agency relationships, analyzed by economists.the determination of the significance of the lease in Polish agriculture with the use of agency theory. The theoretical basis is primarily provided by a review of the literature encompassing publications devoted to agency theory, legislative acts pertaining to leases, as well as domestic and foreign scientific studies. Statistical data deriving from the Agricultural Property Agency. The time range of the analysis encompassed the years 1992-2015. The empirical section was prepared on the basis of results of our own studies.According to the analysis of the results of the author's own studies, the most important advantage of leasing for the lessees is the possibility of expanding the farm (76.1%). Very similar importance was also assigned to the possibility of the pre-emptive right (70.1%). Most frequently (42.4%) this answer was indicated by the respondents who held over 75% under lease in total used land. This may be justified by the fact that farms with a high share of lease function in the environment of a relatively higher level of risk than farms with the majority of ownership, whereas purchase of leased land contributes to its minimisation.
Keywords: D82; L51; Q15; 330; agricultural lease; agency theory; contract